Influencing purchase choices: analyzing the interplay between product quality, promotion, and hammerstout products - Aryanda Muhammad Rivaldi; Adam Faritzal (Jurnal Mantik, 2023)
The present study aims to examine the influence of brand image, promotion, and product quality on consumer purchase behavior, with a specific emphasis on Hammerstout items. The fashion industry in Indonesia, encompassing the apparel sector, plays a substantial role in fostering the economic development of the nation. The research utilizes a range of analytical methodologies, including as descriptive statistical analyses, instrumental tests, tests of classical assumptions, double linear regression analyses, and hypothesis testing. The results indicate that the quality of a product plays a substantial role in shaping consumers' purchase choices, accounting for a large proportion of 63.2% in the overall decision-making process. Promotion has a beneficial influence on purchasing decisions, accounting for a significant proportion of 20.1%. The combined factors of product quality and promotion contribute to 83.3% of the impact on consumer purchasing decisions, while the remaining 16.7% is ascribed to other variables